DT2216—a Bcl-xL-specific degrader is highly active against Bcl-xL-dependent T cell lymphomas - He, Yonghan; Koch, Raphael; Budamagunta, Vivekananda; Zhang, Peiyi; Zhang, Xuan; Khan, Sajid; Thummuri, Dinesh; Ortiz, Yuma T.; Zhang, Xin; Lv, Dongwen; Wiegand, Janet S.; Li, Wen; et al. (Journal of hematology and oncology, 2020)
Background Patients with advanced T cell lymphomas (TCLs) have limited therapeutic options and poor outcomes in part because their TCLs evade apoptosis through upregulation of anti-apoptotic Bcl-2 proteins. Subsets of TCL cell lines, patient-derived xenografts (PDXs), and primary patient samples depend on Bcl-xL for survival. However, small molecule Bcl-xL inhibitors such as ABT263 have failed during clinical development due to on-target and dose-limiting thrombocytopenia. Methods We have developed DT2216, a proteolysis targeting chimera (PROTAC) targeting Bcl-xL for degradation via Von Hippel-Lindau (VHL) E3 ligase, and shown that it has better anti-tumor activity but is less toxic to platelets compared to ABT263. Here, we examined the therapeutic potential of DT2216 for TCLs via testing its anti-TCL activity in vitro using MTS assay, immunoblotting, and flow cytometry and anti-TCL activity in vivo using TCL cell xenograft and PDX model in mice. Results The results showed that DT2216 selectively killed various Bcl-xL-dependent TCL cells including MyLa cells in vitro. In vivo, DT2216 alone was highly effective against MyLa TCL xenografts in mice without causing significant thrombocytopenia or other toxicity. Furthermore, DT2216 combined with ABT199 (a selective Bcl-2 inhibitor) synergistically reduced disease burden and improved survival in a TCL PDX mouse model dependent on both Bcl-2 and Bcl-xL. Conclusions These findings support the clinical testing of DT2216 in patients with Bcl-xL-dependent TCLs, both as a single agent and in rational combinations.